Healthcare professionals' views about how pregnant women can benefit from using a closed‐loop system: Qualitative study. Issue 5 (7th March 2023) - Lawton, Julia; Rankin, David; Hartnell, Sara; Lee, Tara; Dover, Anna R.; Reynolds, Rebecca M.; Hovorka, Roman; Murphy, Helen R.; Hart, Ruth I.; ,
Abstract: Background: Interest is growing in how closed‐loop systems can support attainment of within‐target glucose levels amongst pregnant women with type 1 diabetes. We explored healthcare professionals' views about how, and why, pregnant women benefitted from using the CamAPS FX system during the AiDAPT trial. Methods: We interviewed 19 healthcare professionals who supported women using closed‐loop during the trial. Our analysis focused on identifying descriptive and analytical themes relevant to clinical practice. Results: Healthcare professionals highlighted clinical and quality‐of‐life benefits to using closed‐loop in pregnancy; albeit, they attributed some of these to the continuous glucose monitoring component. They emphasised that the closed‐loop was not a panacea and that, to gain maximum benefit, an effective collaboration between themselves, the woman and the closed‐loop was needed. Optimal performance of the technology, as they further noted, also required women to interact with the system sufficiently, but not excessively; a requirement that they felt some women had found challenging. Even where healthcare professionals felt that this balance was not achieved, they suggested that women had still benefitted from using the system. Healthcare professionals reported difficulties predicting how specific women would engage with the technology. In light of their trial experiences, healthcare professionals favoured an inclusive approach to closed‐loop rollout in routine clinical care. Conclusions: Healthcare professionals recommended that closed‐loop systems be offered to all pregnant women with type 1 diabetes in the future. Presenting closed‐loop systems to pregnant women and healthcare teams as one pillar of a three‐party collaboration may help promote optimal use.